Cardiovascular findings on computed tomography in patients with unclear finding situation and trauma of unknown origin. Issue 42 (October 2017) - Meyer, Hans-Jonas; Schramm, Dominik; Bach, Andreas Gunter; Beeskow, Anne; Surov, Alexey
Abstract : Abstract: Incidental cardiovascular findings are common and can be found in up to 70% of patients. Previously, several reports about incidental findings (IFs) on whole body computed tomography (CT) were published. However, no previous study investigated cardiovascular IFs in patients with unclear finding situation and trauma of unknown origin on whole body CT. The radiological database of 2 university hospitals was screened for patients with trauma of unknown origin and unclear finding situation investigated by whole body CT. The images were retrospectively analyzed by 2 radiologists in consensus. The findings were classified according to their clinical relevance. Clinically nonrelevant findings like valvular sclerosis, aortic sclerosis, or anatomic variants were excluded from this study. Moreover, the radiology reports were analyzed to assess initial reporting by the radiologist. Overall, we identified 60 patients with a mean age of 63 years. A total of 98 clinically relevant cardiovascular IFs (CRCIF) were identified in 60 (75%) patients (1.6 CRCIF per patient). The most prevalent finding was cardiomegaly in 23 patients, followed by coronary sclerosis in 21 patients and aortic ectasia in 11 patients; other findings were rarer. Sixty-one findings were reported (62.2%) and 37 were nonreported (37.8%). Thirty patients (50%) showed no traumatic event on whole body CT. CRCIFs are common in patients with unclear finding situation and trauma of unknown origin. Despite initial indication for trauma detection, the whole body CT should carefully be evaluated for CRCIF because of the high prevalence of clinically relevant findings. Notably, 37.76% of the findings were not reported by the radiologist.